Is the Onion Router a Secure Network? - Donald L., Buresh (Journal of Advanced Forensic Sciences, 2020)
This paper attempts to answer the question of how government agencies use The Onion Router, or Tor, in conducting investigations. The essay observes that Tor is free open-source software that can be used by anyone who desires to communicate with others in a secure manner. In surveying the literature, it is found that Tor can be employed for both legal and illegal purposes. As the major financial contributor, Tor is used by government to secure its communications. Because Tor by bad actors, and because many of the Tor relays are operated by government agencies, Tor has been successfully employed in catching unsuspecting criminals. The conclusion of this exposition is that if one wants to communicate securely with someone else, and not be visible to government agencies, Tor should not be the vehicle of choice. There are alternative modes of communication that can thwart the risk of government surveillance.
Keywords: NSA; The Onion Router; TOR; Virtual Private Network; VPN